PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI MATRIKS SISWA KELAS XI MIA SMAN 6 KOTA JAMBI - Yeni Purwati; Buyung Buyung; Relawati Relawati (Universitas Batanghari Jambi, 2018)
Abstract: This study aims to develop LKS and knowing the quality of the LKS developed in the aspect of validity, practicality, and effectiveness. The development of this LKS done on the material matrix of Class XI MIA SMAN 6 city of Jambi. This type of research is the development of research or Research & Developmet (R&D). This study refers to the ADDIE (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). Assessment instruments used in this development is LKS by expert validation sheet material, design experts, media experts, the evaluation sheet, pre-test and post test. The quality of LKS onaspects of validity views based on validation by experts that is meets the criteria is very good and very viable with overall average 4.14 as well as the overall percentage of 82.9%. On the practicality of views based on the results of the evaluation of field trials by students that is meet the criteria of good and viable with average 4.00 sera overall percentage of 81%. While on the effectiveness of views based on a calculation t count (th) from the results of pre-test and post-test earned amounting to 23.39 and t table (tt) of 2.02 so th greater than tt. This shows that the hypothesis was accepted and acknowledged there were significant differences between the pre-test and post-test. Calculation based on the development of LKS based PBL was declared effective.Keywords: Student Worksheet (LKS), Matrix, Development, Problem Based Learning (PBL).